Dimeric Pillar[5]arene as a Novel Fluorescent Host for Controllable Fabrication of Supramolecular Assemblies and Their Photocatalytic Applications. Issue 9 (22nd January 2023) - Wang, Kaiya; Zhang, Rongbo; Song, Zejing; Zhang, Kaituo; Tian, Xueqi; Pangannaya, Srikala; Zuo, Minzan; Hu, Xiao‐Yu
Abstract: A dimeric fluorescent macrocycle m ‐TPE Di‐EtP5 (meso‐tetraphenylethylene dimeric ethoxypillar[5]arene) is synthesized based on the meso ‐functionalized ethoxy pillar[5]arene. Through the connectivity of two pillar[5]arenes by CC double bond, the central tetraphenylethylene (TPE) moiety is simultaneously formed. The resultant bicyclic molecule not only retains the host–guest properties of pillararenes but also introduces the interesting aggregation‐induced emission properties inherent in the embedded TPE structure. Three dinitrile derivatives with various linkers are designed as guests (G1, G2, and G3 ) to form host–guest assemblies with m ‐TPE Di‐EtP5 . The morphological control and fluorescence properties of the assemblies are successfully realized. G1 with a shorter alkyl chain as the linker completely threads into the cavities of the host. G2, due to its longer chain length, forms a linear supramolecular polymer upon binding to m ‐TPE Di‐EtP5 . G3 differs from G2 by possessing a bulky phenyl group in the middle of the chain, which can be further assembled with m ‐TPE Di‐EtP5 to form supramolecular layered polymer and precipitated out in solution, and can be efficiently applied to photocatalytic reactions. Abstract : A dimeric fluorescent macrocycle m ‐TPE Di‐EtP5 is synthesized based on the meso ‐functionalized ethoxy pillar[5]arene. Three dinitrile derivatives (G1, G2, and G3 ) with different linkers are designed as guests to form host–guest assemblies with m ‐TPE Di‐EtP5 . The assembly of m ‐TPE Di‐EtP5⊃G3 forms layered supramolecular polymer and is applied efficiently for photocatalysis in aqueous solution.